Vitamin D levels in critically ill patients with acute kidney injury: a protocol for a prospective cohort study (VID-AKI). Issue 7 (12th July 2017) - Cameron, Lynda Katherine; Lei, Katie; Smith, Samantha; Doyle, Nanci Leigh; Doyle, James F; Flynn, Kate; Purchase, Nicola; Smith, John; Chan, Kathryn; Kamara, Farida; Kidane, Nardos Ghebremedhin; Forni, Lui G; et al.
Abstract : Introduction: Acute kidney injury (AKI) affects more than 50% of critically ill patients. The formation of calcitriol, the active vitamin D metabolite, from the main inactive circulating form, 25-hydroxyvitamin D (25(OH)D), occurs primarily in the proximal renal tubules. This results in a theoretical basis for reduction in levels of calcitriol over the course of an AKI. Vitamin D deficiency is highly prevalent in critically ill adults, and has been associated with increased rates of sepsis, longer hospital stays and increased mortality. The primary objective of this study is to perform serial measurements of 25(OH)D and calcitriol (1, 25(OH)2 D), as well as parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) levels, in critically ill adult patients with and without AKI, and to determine whether patients with AKI have significantly lower vitamin D metabolite concentrations. The secondary objectives are to describe dynamic changes in vitamin D metabolites, PTH and FGF23 during critical illness; to compare vitamin D metabolite concentrations in patients with AKI with and without renal replacement therapy; and to investigate whether there is an association between vitamin D status and outcomes. Methods and analysis: 230 general adult intensive care patients will be recruited. The AKI arm will include 115 critically ill patients with AKI Kidney Disease Improving Global Outcome stage II or stage III. The comparison group will include 115 patients who require cardiovascular or respiratory support, but who do not have AKI. Serial measurements of vitamin D metabolites and associated hormones will be taken on prespecified days. Patients will be recruited from two large teaching Trusts in England. Data will be analysed using standard statistical methods. Ethics and dissemination: Ethical approval was obtained. Upon completion, the study team will submit the study report for publication in a peer-reviewed scientific journal and for conference presentation. Trial registration number: NCT02869919; Pre-results.